Grammatical aspect and temporal distance in motion descriptions - Anderson, Sarah; Matlock, Teenie; Spivey, Michael (Frontiers in Psychology, 2013)
Grammatical aspect is known to shape event understanding. However, little is known about how it interacts with other important temporal information, such as recent and distant past. The current work uses computer-mouse tracking (Spivey, Grosjean, & Knoblich, 2005) to explore the interaction of aspect and temporal context. Participants in our experiment listened to past motion event descriptions that varied according to aspect (simple past, past progressive) and temporal distance (recent past, distant past) while viewing scenes with paths and implied destinations. Participants used a computer mouse to place characters into the scene to match event descriptions. Our results indicated that aspect and temporal context interact in interesting ways. When aspect placed emphasis on the ongoing details of the event and the temporal context was recent (thus, making fine details available in memory), this match between conditions elicited smoother and faster computer mouse movements than when conditions mismatched. Likewise, when aspect placed emphasis on the less-detailed end state of the event and temporal context was in the distant past (thus making fine details less available), this match between conditions also elicited smoother and faster computer mouse movements.